The Effect of Compensation on Work Productivity of Physiotherapists in Yogyakarta - Daru Kumoro Cipto Jati; Umi Budi Rahayu; Siti Soekiswati; Dwi Rosela Komala Sari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The growing demand for physiotherapy services has challenged work productivity and job satisfaction among physiotherapists in many healthcare facilities. Inadequate financial compensation is a primary source of stress that can affect both job satisfaction and productivity. This study aims to analyze the effect of compensation on the work productivity of physiotherapists in Yogyakarta. This study employed a quantitative method with a correlational design. The sample consisted of 75 physiotherapist respondents in Yogyakarta, selected using total population sampling. The independent variable was compensation, and the dependent variable was work productivity, which was measured using a questionnaire. Data were analyzed using Simple Linear Regression analysis with SPSS version 27. The results show that compensation has a significant positive effect on work productivity (b = 0.768; t-test = 7.131; p < 0.001) and job satisfaction (b = 0,750; t-test = 5,122; p<0,001) among physiotherapists in Yogyakarta. This indicates that better compensation for physiotherapists in Yogyakarta will improve their work productivity. It is recommended that a policy be established to standardize compensation, making it fairer and more proportional according to physiotherapists workload and qualifications. This policy should institute clear and uniform regulations governing the calculation of salaries and allowances for all physiotherapists, thereby eliminating arbitrariness and ensuring accountability.